Capstone final paper: in what ways can we make pedagogical documentation more meaningful or accessible for multilingual families? - Yee, Sabrina (My University, 2026)
This capstone paper explores how pedagogical documentation can be made more meaningful and accessible for multilingual families in an early childhood setting. The project is situated within The Center for New Canadians (Pseudonym), where I worked alongside educators, children, and families from diverse cultural and linguistic backgrounds. In this context, many families and educators speak languages other than English, which can shape how they engage with and interpret pedagogical documentation. Using a qualitative research approach, I worked with educators and gathered feedback from families to explore their experiences with pedagogical documentation practices. Data was generated through educator focus groups, questionnaires, family feedback, and observations from documentation within the centre. In response to these insights, I also co-created a learning story with an educator to explore how families engage with documentation when different modes are used. The findings show that while families value documentation as a way to understand their child’s learning, language barriers and too much text can limit accessibility and engagement. Families expressed a preference for including home languages and visual elements, such as photos and videos, to support understanding and connection between home and school. This research also examines both the possibilities and challenges of creating more inclusive pedagogical documentation practices. It highlights how incorporating home languages, visual elements, and multimodal forms of communication can enhance accessibility and strengthen family engagement. At the same time, it also considers the challenges of time constraints, available resources, and differences in families' language proficiency and preferred ways of understanding and accessing information within early childhood settings.
Keywords: multilingual families; pedagogical documentation; The Centre for New Canadians; qualitative research; early childhood settings